Operationalising the 15-minute city with New Mobility services: Artikel - Martin, Robert Joseph (Proceedings from the Annual Transport Conference at Aalborg University, 2024)
The 15-minute city concept has gained significant traction in recent years but faces implementation challenges across diverse geographical, spatial, and political contexts. This 15-minute concept proposes that primary functions should be accessible within 15 minutes by walking, cycling, or public transport. However, it provides little guidance on the placement of these functions or the modalities of access. Additionally, it does not consider various new mobility modes and services, nor emerging technologies such as telecommuting and e-commerce. The main challenge is that the 15-minute city presents an alternative planning paradigm to the existing automobility paradigm, which has dominated global city planning over the past century. While cars can facilitate all types of trips, no other transport mode can claim the same versatility. To transition to a new mobility paradigm, we must consider unbundling these trips to allow for the rightsizing of vehicles according to trip purposes, better aligning with factors such as cost, environmental impact, and spatial constraints. This article will showcase how the New Mobility Assessment Framework has been applied to the new development of Hinna Park, outside of Stavanger, Norway. The project provides insights for the public transport authority, Kolumbus, on optimising the deployment of shared mobility services such as bikes, e-bikes, e-scooters, shared cars, and car-pooling. It also provided insights to allow key discussions between Kolumbus and the property developer to plan the new districts to support sustainable modes of transport. The framework aims to operationalise the mobility principles of the 15-minute city through public-private collaboration, assessing market potential, setting ambition levels for behaviour change, and developing pricing and investment strategies.